2022
DOI: 10.1093/ibd/izac062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with Respiratory Symptoms Among Patients with Inflammatory Bowel Disease: A Prospective Study

Abstract: Background No large, prospective study has investigated respiratory symptoms in patients with inflammatory bowel diseases. We aimed to describe the prevalence of and factors associated with respiratory symptoms in patients with inflammatory bowel disease. Methods In an observational, prospective, cross-sectional study, we evaluated the frequency of respiratory symptoms using a validated self-reporting questionnaire from Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Numerous studies have been conducted in recent years to investigate the mechanisms linking OSA and GID and to establish a causal relationship between 2 , 3 , 23 . Recent studies have revealed that OSA-induced physiological changes, such as intermittent hypoxaemia and sleep disruption, may increase the risk of GID, including gastroesophageal reflux disease, gastric ulcers, and another digestive disorders 20 22 . The increased stress on the body’s internal environment caused by OSA may precipitate gastrointestinal dysfunction 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have been conducted in recent years to investigate the mechanisms linking OSA and GID and to establish a causal relationship between 2 , 3 , 23 . Recent studies have revealed that OSA-induced physiological changes, such as intermittent hypoxaemia and sleep disruption, may increase the risk of GID, including gastroesophageal reflux disease, gastric ulcers, and another digestive disorders 20 22 . The increased stress on the body’s internal environment caused by OSA may precipitate gastrointestinal dysfunction 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic obstructive pulmonary disease (COPD) is a common lung in ammatory airway disease, which has been found to have a strong association with gastrointestinal diseases (10,11). According to meta-analyses and observational studies reported, 13.7% of patients with IBD reported COPD (12), and COPD severity is also related to IBD risk, the incidence of UC was 30% higher in the COPD population, and 61% for CD (13,14). Since IBD and COPD shared many common factors, such as embryonic structure, immune characteristics, and environmental risk factors (15).…”
Section: Introductionmentioning
confidence: 99%